Konsep Dakwah dan Jihad Sulthan Mahmud Badaruddin II - Amin Sihabuddin (Wardah, 2016)
Abstrak:This article explain tentang about dakwah conceptand jihad by Sulthan Mahmud Badaruddin II Palembang. While the main purpose of this paper is to find a correlation between propaganda and jihad Sulthan Mahmud Badaruddin II Palembang. Research would like to know, first, how the thought of preaching Sulthan Mahmud Badaruddin II. Second, how the activity of preaching and jihad Sulthan Mahmud Badaruddin II. Third, the effect of propaganda Sulthan Mahmud Badaruddin II in Palembang. Through this research will benefit obtained. First, to get the information, data, and biographies about Sulthan Mahmud Badaruddin II. Second, gain knowledge about the fight Sulthan Mahmud Badaruddin II in developing a missionary. The influence of propaganda and jihad Sulthan Mahmud Badaruddin II are felt to this day. While the influence of propaganda and jihad Sulthan Mahmud Badaruddin II Palembang, public awareness has spawned Palembang to unite and build a better again.